The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s13277-015-4751-x
|View full text |Cite
|
Sign up to set email alerts
|

Silencing A7-nAChR levels increases the sensitivity of gastric cancer cells to ixabepilone treatment

Abstract: Gastric cancer is an important health issue worldwide. Currently, improving the therapeutic efficacy of chemotherapy drugs is an important goal of cancer research. Alpha-7 nicotine acetylcholine receptor (A7-nAChR) is the key molecule that mediates gastric cancer progression, metastasis, and therapy responses; however, the role of A7-nAChR in the therapeutic efficacy of ixabepilone remains unclear. A7-nAChR expression was silenced by small interfering RNA (siRNA) technology. The cytotoxicity of ixabepilone was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The reduced sensitivity of gastric cancer to cisplatin under the influence of nicotine was largely blocked by siRNA targeting the CHRNA5 gene, which encodes α5 subunit of nAChR [12]. Knockdown of α7 nAChR increased the sensitivity of gastric cancer cells to taxan and ixabepilone [13]. Nicotine contributed to the survival of pancreatic cancer cells, leading to protein kinase B (AKT) phosphorylation and activation of atypical protein kinase C, while mecamilamine, a non-specific nAChR blocker, reduced this effect [14].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced sensitivity of gastric cancer to cisplatin under the influence of nicotine was largely blocked by siRNA targeting the CHRNA5 gene, which encodes α5 subunit of nAChR [12]. Knockdown of α7 nAChR increased the sensitivity of gastric cancer cells to taxan and ixabepilone [13]. Nicotine contributed to the survival of pancreatic cancer cells, leading to protein kinase B (AKT) phosphorylation and activation of atypical protein kinase C, while mecamilamine, a non-specific nAChR blocker, reduced this effect [14].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the homo-pentameric α7 nAChRs belong to the most ancient branch of this receptor family and are expressed in neurons and non-excitable cells, where they mediate pro-proliferative and anti-inflammatory signaling. Gastric cancer cells, where α7 nAChR expression was knocked-down, showed resistance to 5-fluorouracil (5-FU), a clinically used chemotherapeutic agent [84] but were reportedly more sensitive to docetaxel, paclitaxel and ixabepilone treatment [85,86]. The specific role of mitochondrial nAChRs versus the plasma membrane-located channel was not addressed in these studies.…”
Section: Defective Mitochondrial Outer Membrane Permeabilization Amentioning
confidence: 99%
“…α7-nAChR pathway activation promotes tumor cell proliferation and inhibits apoptosis via PI3K/AKT signaling pathways [27]. Recent studies suggest that some chemotherapeutic drugs, including 5-Fluorouracil and Ixabepilone, can downregulated α7-nAChR and promote gastric cancer cell apoptosis through the AKT pathway [28,29]. The rabies virus glycoprotein has nicotine receptor blocking function similar to that of coral snake venom [10].…”
Section: Discussionmentioning
confidence: 99%
“…NDV has been explored as an oncolytic agent [7,8]. Acetylcholine receptors (AChR) are highly expressed in non-small cell lung cancer, gastric cancer, bladder cancer, and colorectal cancer [9]. Many studies have found that α7-nAChR affects expression and activation of cancer cell proliferation, invasion, metastasis, angiogenesis, and the inflammatory response [1012].…”
Section: Introductionmentioning
confidence: 99%